2020
DOI: 10.1016/j.techfore.2019.119766
|View full text |Cite
|
Sign up to set email alerts
|

Founder Personalities, Behaviors and New Venture Success in Sub-Saharan Africa

Abstract: Facing heightened levels of political instability and institutional fragility, several sub-Saharan African countries have been responding with innovation policies and entrepreneurship support structures. With little scholarly knowledge on who those entrepreneurs are at an individual level, however, the ability to effectively support innovative new ventures in some of the world's most compromised regions would remain limited. Based on a sample of 232 entrepreneurs, this study attempts to enlighten the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…Our results also suggest that a descendant entrepreneur with openness trait (i.e., intellectually curious, inventive, unorthodox) may contribute more toward the successful succession of small family businesses (H1a is accepted). The results of hypothesis H1a is consistent with the findings of Rashid et al (2020) , Botero et al (2021) , and Zhou et al (2022) . Botero et al (2021) revealed that the openness personality trait has a significant relationship with job performance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results also suggest that a descendant entrepreneur with openness trait (i.e., intellectually curious, inventive, unorthodox) may contribute more toward the successful succession of small family businesses (H1a is accepted). The results of hypothesis H1a is consistent with the findings of Rashid et al (2020) , Botero et al (2021) , and Zhou et al (2022) . Botero et al (2021) revealed that the openness personality trait has a significant relationship with job performance.…”
Section: Discussionsupporting
confidence: 88%
“… Botero et al (2021) revealed that the openness personality trait has a significant relationship with job performance. Zhou et al (2022) found that openness trait entrepreneurs have a significant association with financial and business growth performance and the success of small and local businesses ( Rashid et al, 2020 ). Retail small family businesses expanding their operation’s diversity and introducing innovative products in a developing country like Pakistan may increase their profitability and expand customer segments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has already emphasized the importance of individual characteristics of the founding entrepreneur for entrepreneurial success [17] and IE [4,18,19]. Not surprisingly, well-established concepts in the IE literature like entrepreneurial orientation (EO) or a global mindset consist of cognitive elements [5].…”
Section: The Roles Of Proactive Behavior and Attitude Towards Ie For mentioning
confidence: 99%
“…In the past, many researchers explore the relationship between individual personality and social behaviours (Manaf et al , 2018; Ali, 2019). Furthermore, Rashid et al (2020) attempt to explain the differences in people's job performance and career achievement by individuals' personality traits. However, those research studies collect users personality by self-reported questionnaires, which are costly and may result in some degree of response subjectivity.…”
Section: Discussionmentioning
confidence: 99%